Improving Product Display of E-commerce Website through Aesthetics, Attractiveness and Interactivity - Syahrul Nizam, Junaini; Jonathan, Sidi (Faculty of Computer Science & Information Technology, Universiti Malaysia Sarawak (UNIMAS), 2005)
In the development process of online store, the attributes of the product view is very important. The fundamental problem that motivated this study is to find the factors that determine customer acceptance of virtual stores especially related with the product display. Through an experimental study, the features of jcpenney.com, victoriassecret.com and adidas.com have been analyzed with respect to aesthetics, attractiveness and interactivity. We present a theoretical framework that highlights the relative importance of these attributes of display to attract customers. Results of this research are expected to provide a basis for better design and display of product at the online store. The results recommend improved guidelines for product display on e-commerce website. We present, from our experience and conclude with suggestions for design and evaluation of product display at the online store.